Changes in the Living Conditions of the Inhabitants of Navoi Region (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this scientific research article, the changes in the social life conditions of the residents of the new industrial cities Navoi, Zarafshan, Uchkuduk in the Kyzylkum desert are highlighted by the author, relying on archival data, scientific literature and magazines, and statistical data. Also, the statistical analysis of problems and achievements of the industrial products produced in the Navoi region today enriches the scientificity of the article.